Evaluation of the botanical origin of commercial dry bee pollen load batches using pollen analysis: a proposal for technical standardization - Barth,Ortrud M. (2010)
High quality of bee pollen for commercial purpose is required. In order to attend the consumer with the best identification of the botanical and floral origin of the product, 25 bee pollen batches were investigated using two techniques of pollen grain preparation. The first started to identify pollen loads of different colors in two grams of each well mixed batch, and the second to identify pollen grains in a pool made of all the pollen loads comprised in two grams. The best result was obtained by this last technique, when a pollen grain suspension was dropped on a microscope slide and circa 500 pollen grains were counted per sample. This analysis resulted in the recognition of monofloral and bifloral pollen batches, while the use of the first technique resulted in all samples receiving a heterofloral diagnosis.